Without due process : a J.P. Beaumont novel - Jance, Judith A. (Jance, Judith A. J. P. Beaumont mysteries, 2012)
Investigations into the murders of Officer "Gentle Ben" Weston's and his family divulges the truth behind his involvement with gangs.